Thomas Kelly Cheyne - Toy, Crawford Howell (1916)
The appearance of the last product of Dr. Cheyne's pen offers occasion to review briefly his work, and to estimate it as far as is now possible, bearing in mind that the significance of a scholar's work is not always clearly visible till some time after he has ceased to be active.